Metabolic issues in patients affected by schizophrenia: clinical characteristics and medical management - Ventriglio, Antonio; Gentile, Alessandro; Stella, Eleonora; Bellomo, Antonello (Frontiers in Neuroscience, 2015)
Patients affected by psychotic disorders are more likely to develop high rates of co-morbidities, such as obesity, type 2 diabetes, dyslipidemias, hypertension, metabolic syndrome, myocardial infarction, stroke etc., in the long-term. These morbidities have a significant impact on the life-expectancy of these patients. Patients with chronic psychoses show a 2–3-fold increased risk of death mostly from cardiovascular and metabolic diseases. Although there may be an independent link, between schizophrenia and metabolic conditions the cardio-metabolic risk is mostly related to an unhealthy lifestyle and the usage of antipsychotic agents (especially Second Generation Antipsychotics or atypical) even when these remain effective treatments in the management of major psychoses. Recently, many international organizations have developed screening and monitoring guidelines for the control of modifiable risk factors in order to reduce the rate of co-morbidity and mortality among patients affected by schizophrenia. This paper is a review of current knowledge about the metabolic issues of patients affected by schizophrenia and describes clinical characteristics and medical management strategies for such conditions.